Strengthening Media Literacy In Personal Data Protection And Understanding Online Loan Fraud Modes - Ita Musfirowati Hanika; Gede Ryan Pratama Putra; Muhammad Nur Ahadi; Farah Mulyasari; Wahyudi Marhaen Pratopo Eko Setyatmojo; Mohammad Ichlas El Qudsi (International Journal of Community Service (IJCS), 2026)
The low level of media literacy among Indonesian communities, combined with the rapid growth of digital media use, has increased public vulnerability to various online risks, particularly illegal online lending practices, digital hoaxes, and personal data misuse. This program aims to analyze the effectiveness of the community outreach initiative “Smart Digital: Protect Your Personal Data and Understand Online Loan Scam Mechanisms” in enhancing public awareness and critical understanding of digital risks. The program was conducted in two sessions using interactive lectures, case-based discussions, simulation activities, and the introduction of the digital verification platform intelligent.digital, involving 56 participants from vulnerable community groups. The evaluation employed a pre-test and post-test design to measure changes in participants' cognitive and psychological aspects. The results indicate a significant improvement in participants' ability to distinguish between legal and illegal online lending services, identify digital hoaxes, and recognize the importance of personal data protection. In addition, participants demonstrated increased risk awareness and proactive behavior in verifying information before making digital decisions. These findings confirm that media literacy is not merely theoretical knowledge, but a fundamental competence required to strengthen public resilience in navigating an increasingly complex and manipulative digital information environment.